Հայաստանի գիտահետազոտական առաջին ինստիտուտը (Էջմիածնի կուլտուր-պատմական ինստիտուտի հիմնադրման 90-ամյակի առթիվ) - Ստեփան Ղարիբջանյան (ՀՀ ԳԱԱ հրատ.)
5 февраля 1921 г. декретом Ревкома и Наркомпроса Армении были национализированы и переданы в непосредственное ведение Наркомпроса ССРА культурно-просветительные и церковные учреждения Эчмиадзина–матенадаран, музей, типография, храм Рипсимэ, развалины собора Звартноц с прилегающими постройками и т. д. On February 5, 1921 by the decree of the Revolutionary Committee of Armenia and Narcompros were nationalized and transferred to the direct supervision of Narcompros SSRA cultural-educational and ecclesiastical foundations of Echmiadzin – Matenadaran, the museum, the printing house, the temple of Hripsime, the ruins of the Zvartnots cathedral with adjoining buildings, etc.
Keywords: History; D History; G Geography; Anthropology; Recreation; GCC Culture and Cultural Processes